Field Verification Trial of ND I-2 Vaccine in Nepal - Acharya, M. P.; Adhikari, S. K.; Awasthi, H.; Jha, A.; Singh, U. M. (Nepalese Veterinary Journal, 2019)
A study was conducted to assess the overall performance of ND I-2 vaccine in Nepalese context to prevent Newcastle disease (ND) particularly in backyard chicken. The experimental studies were conducted at Animal Health Research Division (AHRD), NARC and field verification were carried out in different eco-zones of the country. Experiments were divided in three segments: evaluation of thermostability, longevity and field verification trial in backyard chickens. The ND I-2 vaccine was prepared at Central Biological Production Laboratory (CBPL), Tripureshwor. In thermostability evaluation antibody titer and mortality percentage showed that ND I-2 vaccine exposed up to 30°C for seven days was found effective in prevention of Newcastle Disease in village chickens. Evaluation of longevity of immunity showed that till 90 days there was protective immunity against ND and in field trials when vaccine delivered without maintaining cold chain, the vaccine gave protective immunity in mid hills and high hills region but not enough immunity in the terai region where the temperature was above 30° Celsius. This study clearly indicated that thermostable ND I-2 vaccine can be used without cold chain in high hills and mid hills in all seasons and only in winter season in the terai region of Nepal (temp. less than 30°C). In summer season, vaccination in the terai region could not give protective immunity (temp. more than 30°C) without maintaining cold chain.